Língua e cultura na sociedade Apinayé (Revista Cocar, 2016)
Neste trabalho, apresentamos um estudo sobre Etnolinguística, Língua e Cultura na Sociedade Indígena Apinayé. O objetivo é, a partir de um estudo teórico, avaliarmos e entendermos a relação ente língua e cultura no contexto indígena Apinayé, identificando como os aspectos sociohistóricos e culturais interferem na situação linguística dos indígenas. As bases teóricas, numa concepção interdisciplinar, abrangem as seguintes áreas:" Linguística, Fiorin (2003); Etnolinguística, Rodrigues (1986, 2001), Oliveira (s/d); Língua Apinayé, Ham (1979), Albuquerque (1999, 2007, 2008; 2012); Os Apinayé, Nimuendaju (1983), Da Matta (1976), Albuquerque (2007); Almeida (2012); e Cultura, Gomes (2013), Cuche (1999). O estudo se insere na perspectiva da pesquisa qualitativa, a partir dos procedimentos das pesquisas exploratórios e documentais. Os resultados da pesquisa permitem afirmar que os Apinayé são bilíngues, pois interagem com duas línguas, Apinayé e Português, em situação de contato e uso."Palavras-chave: Etnolinguística; Cultura; Apinayé."Language and culture in Apinayé society"In this paper, we present a study on Ethnolinguistics, Language and Culture in Apinayé Indigenous Society. From a theoretical study, the goal is to evaluate and understand the language and culture being compared in an Apinayé indigenous context, identifying how the socio-historical aspects and cultural influence the language situation of indigenous peoples. The theoretical basis, in an interdisciplinary design, cover the following areas of linguistics: Fiorin (2003). Ethnolinguistics: Rodrigues (1986, 2001), Oliveira (s/d); Language Apinayé, Ham (1979), Albuquerque (1999, 2007, 2008, 2012); Apinayé people, Nimuendaju (1983), Da Matta (1976), Albuquerque (2007); Almeida (2012); and Culture, Gomes (2013), Cush (1999). The study is insert in the perspective of qualitative research, from procedures of exploration and documentary research. The survey results allow us to state that Apinayé are bilingual, because they interact with two languages, Apinayé and Portuguese, in contact situation and use.Keywords: Ethnolinguistics; Culture; Apinayé.